Improved assembly of bispecific antibodies from knob and hole half‐antibodies. (15th July 2015) - Williams, Ambrose Jon; Giese, Glen; Persson, Josefine
<x xml:space="preserve">Abstract</x> A process was developed for large‐scale assembly of IgG1 and IgG4 bispecific antibodies from knob and hole half‐antibodies. We optimized assembly conditions such as pH, temperature, stabilizers, and reducing agent. We also identified and exploited structural changes unique to knob and hole half‐antibodies with the result of improving assembly outcome, specifically storing half‐antibodies at higher pH will condition them to assemble more rapidly and produce fewer high molecular‐weight species (HMWS). Application of heat to the assemblies resulted in an acceleration of assembly rate, with optimal formation of bispecific achieved at 37°C. IgG4 half‐antibodies were unusually sensitive to temperature‐dependent formation of HMWS in pre‐assembly conditioning as well as during assembly. We selected l‐histidine and Polyvinylpyrrolidone (PVP) as stabilizers to prevent HMWS formation in IgG4, and achieved rapid and high‐efficiency assemblies. Using optimized assembly conditions, we developed and scaled up a method for assembling bispecific antibody with 90% assembly efficiency over 6 h with minimal impact to product quality, generating a pool with bispecific antibody for downstream processing. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1315–1322, 2015